2023
DOI: 10.3390/toxics11020091
|View full text |Cite
|
Sign up to set email alerts
|

Significant Biotransformation of Arsenobetaine into Inorganic Arsenic in Mice

Abstract: Arsenic (As) is extremely toxic to living organisms at high concentrations. Arsenobetaine (AsB), confirmed to be a non-toxic form, is the main contributor to As in the muscle tissue of marine fish. However, few studies have investigated the biotransformation and biodegradation of AsB in mammals. In the current study, C57BL/6J mice were fed four different diets, namely, Yangjiang and Zhanjiang fish diets spiked with marine fish muscle containing AsB, and arsenite (As(III)) and arsenate (As(V)) diets spiked with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Although early toxicokinetic human studies concluded that urinary excretion of seafood-derived AB is fast and efficient [44][45][46][47], later work indicated that intestinal absorption and urinary excretion of AB from seafood diet may not always be efficient [48][49][50]. Recent studies have reported gut-microbiota dependent AB accumulation in mice [51] and hypothesized that under chronic exposure scenarios and depending on the specific AB-containing food matrix, a significant portion of AB may reach the large intestinal lumen, where microbial AB degradation can occur, potentially producing arsenic species of health concern [52]. However, these studies did not definitively establish the causal role of intestinal bacteria in these processes.…”
Section: Introductionmentioning
confidence: 99%
“…Although early toxicokinetic human studies concluded that urinary excretion of seafood-derived AB is fast and efficient [44][45][46][47], later work indicated that intestinal absorption and urinary excretion of AB from seafood diet may not always be efficient [48][49][50]. Recent studies have reported gut-microbiota dependent AB accumulation in mice [51] and hypothesized that under chronic exposure scenarios and depending on the specific AB-containing food matrix, a significant portion of AB may reach the large intestinal lumen, where microbial AB degradation can occur, potentially producing arsenic species of health concern [52]. However, these studies did not definitively establish the causal role of intestinal bacteria in these processes.…”
Section: Introductionmentioning
confidence: 99%
“…After oral intake, these chemicals are transferred to the gastrointestinal tract; however, only a proportion of them can be absorbed by the human body and cause toxic effects. Information on the real absorption of different As species in the human gastrointestinal tract is very limited, but according to some studies with mice, AsB has a significantly higher absorption efficiency (over 96%) than As(III) and As(V) (approximately 81 and 86%, respectively), and significant biotransformation of AsB to [As(V)] following oral administration has been indicated (10). Therefore, fully considering bio-accessibility (the proportion of these chemicals that have undergone possible biotransformation during digestion and can be released from the food matrix for human body absorption) in toxicity evaluation seems to be more accurate than just analyzing the undigested food sample itself.…”
Section: Introductionmentioning
confidence: 99%